Expression of HPV‐related biomarkers and grade of cervical intraepithelial lesion at treatment. (February 2014) - Valasoulis, George; Stasinou, Sofia‐Melina; Nasioutziki, Maria; Athanasiou, Antonis; Zografou, Maria; Spathis, Aris; Loufopoulos, Aristotelis; Karakitsos, Petros; Paraskevaidis, Evangelos; Kyrgiou, Maria
Abstract Objectives New human papillomavirus (HPV)‐related biomarkers may allow better identification of clinically significant lesions that warrant excision and, conversely, identification of the false positive cases that have been overreported by traditional techniques. The aim of this study was to investigate how the expression of several HPV‐related biomarkers correlates to the severity of the lesion at treatment. Design Prospective observational study. Setting University Hospital (2009–2011). Population All women submitted for excisional treatment. Methods A liquid‐based cytology sample was obtained before treatment and was tested for HPV typing, mRNA E6 & E7 with NASBA or flow cytometry and p16. All women had histological diagnosis in the form of excisional cone (gold standard). Main outcome measures Correlation of HPV biomarker positivity rates to the grade of the lesion at treatment histology. Results Two hundred women were recruited: 23 were found to have negative histology (11.5%), 79 (39.5%) CIN1, 50 (25.0%) CIN2 and 48 (24.0%) CIN3. All biomarkers (HPV DNA typing, HR HPV, single HPV 16/18, mRNA E6 & E7 expression and p16) revealed an increased linear positivity rate with increasing severity and grade of the lesion (chi‐squared test for trend p < 0.05). This was stronger for HPV (all and high‐risk) followed by mRNA with NASBA, flow cytometry, HPV 16/18 and ultimately p16 immunostaining. Conclusions The linear correlation between various HPV‐related biomarkers and the grade of the lesion suggests that these biomarkers may prove to be useful in the prediction of CIN grade and, as a result, the need for treatment.